An overview of Holocene climate reconstructions in northernmost Fennoscandia: A contribution to the Stone Age Demographics project - Sjögren, Per J.E. (Septentrio Reports, 2021)
An overview of climate reconstructions considering summer air temperatures and effective precipitation is provided for northernmost Fennoscandia. During the earliest part of the Holocene (11,700–10,000 cal. BP), temperatures rose rapidly and were followed by mild, wet and variable conditions. An early major warming peaked around 9500 cal. BP, although many records indicate that the main Holocene warming first occurred about c. 8000 cal. BP. The sub-regional pattern of climate change suggests a defining influence of the westerlies and the North Cape Current. Non-analog climatic conditions and lags in vegetation responses to climate change may explain some of the discrepancies seen in the early Holocene between proxies. In contrast to the perceivable variable onset of the main Holocene warm period, maximum temperatures are relatively consistent between the records, indicating temperatures 1.5±0.5°C above present. Precipitation was generally high from 10,000 cal. BP but decreased towards 8000 cal. BP when dry climatic conditions became predominant. After a stable period 8000–6000 cal. BP a gradual cooling was initiated, with a more abrupt period of change 4500–3800 cal. BP when the warm and dry climate of the mid-Holocene changed into the cool, wet and unstable climate of the late Holocene. Modern conditions were reached c. 2800 cal. BP. The Holocene Thermal Maximum may be defined several different ways: as temperatures distinctly above modern delimited to 9500–4000 cal. BP; as peak temperatures 9500–6000 cal. BP; and/or as climax vegetation in the period 8000–4000 cal. BP. Prior to 8000 cal. BP vegetation probably lagged behind the warming, whereas in the period 8000–4000 cal. BP an equilibrium between climate and vegetation was established.